Pijat Oksitosin pada Ibu Postpartum sebagai Upaya Meningkatkan Produksi Asi - Feni Noviyani; Moneca Diah Listiyaningsih; Munasifah (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2024)
Breast milk not coming out is a condition where breast milk is not produced or there is little milk production. This is due to the influence of the oxytocin hormone which is not working enough due to the lack of stimulation from the baby's sucking which activates the work of the oxytocin hormone. One of the actions that need to be taken to maximize the quality and quantity of breast milk is back massage. Problems of postpartum mothers in the Sakura Room RST dr. Asmir Salatiga lacks knowledge about how to increase breast milk production with oxytocin massage. The activities were carried out in the Sakura Room, RST. Dr. Asmir Salatiga by providing health education about oxytocin massage as an effort to increase breast milk production. During the health education, oxytocin massage demonstrations were also carried out on 20 postpartum mothers. The instrument used was a questionnaire regarding knowledge of oxytocin massage. Knowledge of postpartum mothers before health education was in the good category of 13 mothers (65%), in the sufficient category of 7 mothers (35%). After health education was carried out, there was an increase in knowledge, namely 20 mothers (100%) mothers with good knowledge about oxytocin massage as an effort to increase breast milk production.This health education activity about oxytocin massage as an effort to increase breast milk production is a means of education and discussion that can provide many benefits for postpartum mothers. Because with this activity, mothers' knowledge about oxytocin massage has increased and they can overcome the problem of inadequate breast milk production that they experience independently by doing oxytocin massage.   ABSTRAK                 ASI tidak keluar adalah kondisi tidak diproduksinya ASI atau sedikitnya produksi ASI. Hal ini disebabkan pengaruh hormon oksitosin yang kurang bekerja sebab kurangnya rangsangan isapan bayi yang mengaktifkan kerja hormon oksitosin. Salah satu tindakan yang perlu dilakukan untuk memaksimalkan kualitas dan kuantitas ASI, yaitu pemijatan punggung. Permasalahan ibu postpartum di Ruang Sakura RST dr. Asmir Salatiga adalah kurangnya pengetahuan tentang cara meningkatkan prouksi ASI dengan pijat oksitosin Pelaksanaan kegiatan dilaksanakan di Ruang Sakura , RST. Dr.Asmir Salatiga dengan memberikan pendidikan kesehatan tentang pijat oksitosin sebagai upaya meningkatkan produkasi ASI. Pada saat melakukan pendidikan kesehatan juga dilakukan demonstrasi gerakan pijat oksitosin pada 20 ibu postpartum. Instrumen yang digunakan adalah kuesioner tentang pengetahuan pijat oksitosin. Pengetahuan ibu postpartum sebelum dilakukan pendidikan kesehatan dalam kategori baik  13 ibu ( 65%), kategori cukup 7 ibu (35%). Pengetahuan setelah dilakukan pendidikan kesehatan terjadi peningkatan pengetahuan yaitu 20  ibu (100%) ibu dengan pengetahuan baik tentang pijat oksitosin sebagai upaya untuk meningkatkan produksi ASI. Kegiatan pendidikan kesehatan tentang pijat oksitosin sebagai upaya meningkatkan produksi ASI  ini menjadi sarana edukasi dan diskusi yang dapat memberikan banyak manfaat bagi ibu postpartum . Karena dengan adanya kegiatan ini pengetahuan ibu  tentang pijat oksitosin mengalami peningkatan dan dapat mengatasi masalah kurang lancarnya produksi ASI yang di alami secara mandiri dengan melakukan pijat oksitosin.